PENGARUH EFIKASI DIRI MATEMATIKA TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA DI MASA PANDEMI COVID-19 - MUHAMMAD AWAL NUR awal (Jurnal Pendidikan Matematika Raflesia, 2022)
The purpose of this study was to determine the magnitude of the effect of mathematics self-efficacy on students' mathematics learning achievement during the Covid-19 pandemic. The research method is ex-post facto quantitative research. The sample in this study was class XI high school students in Bulukumba Regency with a total of 144 students. The data analysis technique in this study is simple linear regression analysis with normality test, linearity test and hypothesis testing using SPSS 16. The results of hypothesis testing indicate that mathematics self-efficacy has a positive and significant effect on mathematics learning achievement of class XI high school students with a significant level of 0, 05 and the value of the regression coefficient of the mathematical self-efficacy variable is 0.240. The magnitude of the effect of mathematics self-efficacy on students' mathematics learning achievement is 18.6%. The conclusion of this study is that mathematics self-efficacy has a positive and significant effect on high school students' mathematics learning achievement.